EFFECTIVENESS OF PNF STRETCHING AND CYCLIC STRETCHING OF CALF TIGHTNESS ON COLLEGE GOING GIRLS (International Journal of Physiotherapy, 2015)
Background: Flexibility helps with injury prevention, the reduction of soreness following a workout, and a general sense of well-being. There are different stretching techniques and protocols for improvements in calf extensibility and flexibility. The purpose of the study was to investigate the effectiveness of two techniques i.e. CYCLIC and PNF stretching which improves calf flexibility. This study was done to find the effectiveness of calf Cyclic and PNF stretching technique to improve calf flexibility.Methods: 30 subjects with age group 21-22 years were randomly allocated to 2 groups equally. Group 1(n=15) were given CYCLIC and group 2(n=15) were given PNF stretching technique. Plantar flexion was used to measure the calf tightness which was done before and after the treatment. Treatment was given for 7 days and on the 7th day the calf tightness was again measured.Results: The mean difference of the CYCLIC is 4.6 and mean difference of PNF is 4.7 which indicate that CYCLIC and PNF both are effective to improve calf flexibility but PNF is more effective than CYCLIC to improve calf flexibility.Conclusion: The neurophysiological basis of PNF, stating that the excitatory efficient of the neuromuscular spindle or the inhibitory afferent of the Golgi tendon organ (GTO) or both are responsible for the effects. During PNF stretch and isometric contraction of stretched agonists for extended period may cause activation of its neuromuscular spindle. The increase in tension created during the isometric contraction of the pre – lengthened agonist contracts concentrically. Both the fascia & the spindle of the agonist adjust to the nearly lengthened position. These impulses travel via causing post synaptic inhibition of the motor neuron to agonist increasing the tension from the GTO. These impulses can override the impulses coming from the neuromuscular spindles arousing the muscle to reflexly resist to the change in length, thus helping in lengthening the muscle.PNF stretching is more effective than cyclic stretching.